Cutting performance of diamond-like carbon coated tips in ultrasonic osteotomy - Yunn-Shiuan Liao; Ting-Chang Lin; Cheng-Yu Lai; Yen-Liang Chen; Hao-Hueng Chang; Chun-Pin Lin (Elsevier, 2014)
Background/purpose: Ultrasonic osteotomy has been introduced in oral and maxillofacial surgery in recent years for minimally invasive treatment. The purpose of this study is to evaluate the cutting performance of three different coated tips by the material removal rate (MRR) measurement and the temperature rise (TR) investigation in ultrasonic osteotomy. Materials and methods: Three stainless steel tips with different coated treatments to have the coefficients of friction of 0.5, 0.4, and 0.1 for uncoated tip, titanium nitride (TiN) coated tip, and diamond-like carbon (DLC) coated tip, respectively, were tested. The tip was fixed in the hand-piece and powered by an ultrasonic device (Cur scale, Bonart, Taiwan) with power mode of 40, 45 and 50. The ultrasonic hand-piece was mounted on the column of the X-Y table, and a uniform down force of 3 N was provided by the voice coil motor. A groove on the bovine bone specimen was obtained as a result of the downward action together with ultrasonic vibration of the tip. The MMR and TR were measured and evaluated. Results: The average MMR for the DLC coated tip under the operation mode 50 of the ultrasonic device was 0.164 mm3/s as compared with 0.153 mm3/s of TiN coated tip and 0.147 mm3/s of the uncoated tip. The average TR in 60 seconds operation was 8.1°C for the uncoated tip, 6.8°C for the TiN coated tip, and 4.5°C for the DLC coated tip. Conclusion: The DLC coated tip leads to the highest material removal rate and least temperature rise among the three types of tip under study. This is due to its low coefficient of friction and less power is needed to overcome the friction force in ultrasonic osteotomy.